Hubungan Intensitas Mengakses Postingan Youtube Yoshiolo Dan Intensitas Komunikasi Peergroup Dengan Perilaku Konsumtif di Bidang Fashion Pada Remaja Di Semarang - Aditya Putra, Mochammad; Noor Rakhmad, Wiwid (Interaksi Online, 2020)
The high level of use of YouTube to view hypebeast review videos can increase the tendency of consumers to behave consumptively towards hypebeast items, because the media is related to the public's mind in receiving information or products that are displayed, one of them through hypebeast review videos on Youtube. A person's desire to appear the same as what is seen from the media encourages consumptive behavior. The desire to be part of the environment, especially in the peer group causes teens to try to follow the trend and the problem is when it is done excessively so that there is a waste and a purchase on the basis of desires not needs that are outside of material capacity. This study aims to determine the Relationship Intensity of Accessing Yoshiolo Youtube Post and Peergroup Communication Intensity with Consumptive Behavior in Fashion in Adolescents in Semarang. Theories used in this research are the Stimulus and Response Theory and Social Exchange Theory. This research is a quantitative research with explanatory type. Researchers used a non-probability sampling technique with a total sample of 60 people aged 18-22 years in the city of Semarang who had seen Yoshiolo's youtube shows and interacted with his peer group. Based on the hypothesis test conducted using Kendall's Tau correlation analysis, it shows that there is a positive relationship in the intensity variable accessing Yoshiolo's youtube postings with the consumptive behavior in fashion in adolescents in Semarang of 0.615 with a significance value of 0,000. Variable intensity of peer group communication with consumptive behavior in fashion in adolescents in Semarang shows a positive relationship with a correlation number of 0.622 and a significance value of 0,000. Field of Fashion in Teenagers in Semarang. With these results, it is recommended to the audience to be more careful in sorting out which information will be digested.